Bi-substitution-induced magnetic moment distribution in spinel BixCo2-xMnO4 multiferroic - SHVETS, IGOR (My University, 2009)
We report the near-edge x-ray absorption spectroscopy (NEXAFS) at the Co/Mn L3,2 edge and oxygen K edge of the well-characterized Bi-substituted Co2MnO4 multiferroic samples. The evolution of peak features in NEXAFS spectra of the Co/Mn L3,2 edge and O K edge show the Bi-induced redistribution of magnetic cations (Co/Mn). The variation in valence states of Co and Mn in all the substituted compositions is consistent with the observed ferrimagnetic behaviour of the samples. Magnetization data show the decrease in molecular f eld complementing the ferrimagnetism. The role of Bi in the enhancement of magnetic interactions as well as the appearance of ferroelectricity in Bix Co2?x MnO4 (0 x 0.3) is discussed.
PUBLISHED
Keywords: TRANSITION-METAL COMPOUNDS; Spectra; X-Ray absorption; colossal magnetoresistance; oxides; Nanoscience & Materials